2005
DOI: 10.1073/pnas.0504614102
|View full text |Cite
|
Sign up to set email alerts
|

Single-stranded DNA mimicry in the p53 transactivation domain interaction with replication protein A

Abstract: One of many protein-protein interactions modulated upon DNA damage is that of the single-stranded DNA-binding protein, replication protein A (RPA), with the p53 tumor suppressor. Here we report the crystal structure of RPA residues 1-120 (RPA70N) bound to the N-terminal transactivation domain of p53 (residues 37-57; p53N) and, by using NMR spectroscopy, characterize two mechanisms by which the RPA͞p53 interaction can be modulated. RPA70N forms an oligonucleotide͞oligosaccharide-binding fold, similar to that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
359
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(384 citation statements)
references
References 49 publications
16
359
2
1
Order By: Relevance
“…The key residues in human p53's DNA binding core domain (including residues 102, 103, 105, 114, 115, 122 and 126) are required for interactions with RAD51, and those in the N-terminal motif (residues 37-57) are required for interactions with RPA. These key amino acid residues are absent in the ∆133p53 protein [36,37]. This might be the reason that ∆133p53 was not co-immunoprecipitated with RAD51 and RPA in this study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The key residues in human p53's DNA binding core domain (including residues 102, 103, 105, 114, 115, 122 and 126) are required for interactions with RAD51, and those in the N-terminal motif (residues 37-57) are required for interactions with RPA. These key amino acid residues are absent in the ∆133p53 protein [36,37]. This might be the reason that ∆133p53 was not co-immunoprecipitated with RAD51 and RPA in this study.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies have shown that the DNA-binding core domain (94-312) of p53 is required for p53-RAD51 interactions, and its N-terminal domain (37-57) is required for p53-RPA interactions [36,37], which suggests that ∆133p53 may not be able to form a complex with these two proteins. We performed a co-immunoprecipitation (co-IP) experiment to test this hypothesis by co-transfecting HA-RAD51 or HA-RPA2 with p53, ∆133p53 or both, into H1299 cells.…”
Section: Rpamentioning
confidence: 88%
“…It is unlikely that the T21A mutation creates a defect in the general conformation of the RPA2 N terminus, because this region is thought to be unstructured (16,17). It is also highly unlikely that antibody recognition of any of the RPA2 phosphoresidues is directly affected by mutation of other sites for the following reasons.…”
Section: Signal (Lane 2)mentioning
confidence: 99%
“…The N-terminal 33 residues of RPA2 undergo both cell cycle-and stress-dependent phosphorylation on approximately nine sites (Fig. 1A), which are thought to exist in an unstructured conformation (16,17). Ser 23 and Ser 29 are constitutively modified during mitosis by cyclin B-Cdk1 (18, 19) and have been suggested to be partially modified beginning at the G 1 /S boundary by the cyclin A-Cdk2 complex (18,20,21).…”
mentioning
confidence: 99%
“…Given that hSSB1 regulates p53 stability and that the hSSB1 homolog RPA has been shown to interact with p53 [29][30][31][32], we examined whether hSSB1 also associates with p53. Following co-immunoprecipitation (co-IP) using Flag-agarose or Myc-agarose, a complex containing hSSB1 and p53 was clearly detected in HEK293T cells overexpressing both exogenous hSSB1 and p53 ( Figure 2A).…”
Section: Hssb1 Interacts With P53 Both In Vitro and In Vivomentioning
confidence: 99%